2017
DOI: 10.15414/jmbfs.2017.6.5.1203-1208
|View full text |Cite
|
Sign up to set email alerts
|

ANTIMICROBIAL ACTIVITY of SPIRULINA PLATENSIS AGAINST AQUATIC BACTERIAL ISOLATES

Abstract: Aquatic organisms are a rich source of novel and bioactive compounds. Cyanobacteria and microalgae being a rich source of bioactive compounds have recently found immense application in human and animal medicine. The present study was attempted to find out the effect of the various extracts of Spirulina platensis, Chlorella vulgaris, Saragassum wightii and Saragassum latifolium using different solvents (methanol, ethanol, ethyl acetate and chloroform) as antimicrobial agents against five bacterial pathogens; S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Elshouny et al reported that Spirulina had stronger antimicrobial activity against S. aureus, E. coli, P. aeruginosa , Salmonella spp., and Shigella spp. than Chlorella vulgaris , Saragassum wightii , and Saragassum latifolium ( Elshouny et al, 2021 ). Additionally, Spirulina methanolic extract was the most effective against tested microorganisms ( Gheda and Ismail, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elshouny et al reported that Spirulina had stronger antimicrobial activity against S. aureus, E. coli, P. aeruginosa , Salmonella spp., and Shigella spp. than Chlorella vulgaris , Saragassum wightii , and Saragassum latifolium ( Elshouny et al, 2021 ). Additionally, Spirulina methanolic extract was the most effective against tested microorganisms ( Gheda and Ismail, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different works have focused on the in vitro antimicrobial activity of several algae extracts against Salmonella spp. [30][31][32][33][34][35][36], L. monocytogenes [19,25,37,38], E. coli [39][40][41][42], S. aureus [43][44][45][46] and B. cereus [47], demonstrating different effectiveness depending on the algae species and extraction process. Others have reported antimicrobial activity referring to the algae species tested in the present study, even if a different extraction process was followed.…”
Section: Discussionmentioning
confidence: 99%
“…) and some FA (Elshouny et al . ) or indirect due the stimulation of the innate or specific immune systems (Ragap et al . ; Yu et al .…”
Section: Economic Feasibility Of Using Spirulina In Aquaculturementioning
confidence: 99%